Circulating endothelial cells as predictor of long-term mortality and adverse cardiovascular outcomes in hemodialysis patients - KOÇ, MEHMET (WILEY, 2021)
Circulating endothelial cells (CEC) are thought to be markers of endothelial injury. We hypothesized that the numbers of CEC may provide a novel means for predicting long-term survival and cardiovascular events in hemodialysis patients. 54 hemodialysis patients underwent enumeration of their CEC number. We retrospectively analyzed their survival and incidence of adverse cardiovascular events. 22 deaths (41%) were noted over the median follow up period of 3.56 years (IQR 1.43-12) and 6 were attributed to cardiovascular deaths (11%) of which 1 (4%) was in the low CEC (CEC<20 cells/ml) and 5 (19%) in the high CEC (CEC >= 20 cells/ml) group. High CEC was associated with worse cardiovascular survival (p = 0.05) and adverse cardiac events (p = 0.01). In multivariate analysis, CEC >20 cells/ml was associated with a 4-fold increased risk of adverse cardiac events (OR, 4.16 [95% CI,1.38-12.54],p = 0.01) while all-cause mortality and cardiovascular mortality were not statistically different. In this hemodialysis population, a single measurement of CEC was a strong predictor of long term future adverse cardiovascular events. We propose that CEC may be a novel biomarker for assessing cardiovascular risk in dialysis patients.
Keywords: DISEASE; CD146